Treatment compliance of Hypertensive Patients (Cardiovascular Journal, 2016)
Background: Hypertension is an important public-health challenge worldwide. It is important because of its high frequency and its effect on cerebrovascular, cardiovascular and kidney disease.Methods: This cross-sectional descriptive study was conducted to assess the treatment compliance of hypertensive patients and medical history of patients with hypertension in the outpatient department of Cardiology, National Institute of Cardiovascular Diseases (NICVD), Dhaka. Considering inclusion and exclusion criteria, 350 hypertensive outdoor patients were included in this study. Data was analyzed by SPSS version 20.Results: The study revealed that the mean age of the respondents was 50.49 years (SD ± 8.449). Approximately 67.2% of the respondents were suffering from hypertension from